The Process of Teaching and Learning Grammar & English Skills - Hani, Umi (CV. Pena Persada, 2018)
Indonesian students learn English as a foreign language. English plays important role as a foreign language. Realizing how important the language is, English is now not only learned by students in English Department, but also by students of junior high school as a compulsory subject. Unfortunately, most of junior high school students still find it difficult to figure out speaking, listening, reading, writing and grammar although the contents of the topic deal with their subjects. As English is a foreign language in Indonesia, students must learn it because it is on the curriculum whether they like it or not. Because of this, the contents of material should be handled in a different way. It is much different from students who are learning English at informal education such as English Course where they learn English ―for fun‖. The course covers the four skills of listening, speaking, reading, and writing, as well as improving pronunciation and building vocabulary. The primary goal of the course is to teach communicative competence, that is, the ability to communicate in English according to the situation, purpose, and roles of the participants. In spite of the fact that many students find difficulties to muster much enthusiasm for the study of speaking, listening, reading, writing, grammatical rules, memorizing vocabulary or practicing pronunciation. Unlike other junior high schools in our country which has larger number of students in the classroom, Insan Harapan School has twenty-four students in each class. With smaller number of students in the class, perhaps the atmosphere of the classroom will be conducive and the interaction between the teachers and the students will be greater and then teacher can dig more individual attention. That is why the writer is interested in investigating how well learning and teaching English is conducted at SMP IT Insan Harapan students as the object of the study. The writer decides in investigating the seventh grade of the students of teaching and learning process.